Causes of visual acuity loss among HIV-infected patients with cytomegalovirus retinitis in the era of highly active antiretroviral therapy in Chiang Mai University Hospital - Tangmonkongvoragul C. (2014)
OBJECTIVE : To quantify the frequencies of the common causes of visual acuity loss for HIV-infected patients with cytomegalovirus retinitis (CMVR) in the era of highly active antiretroviral therapy(HAART). METHODS : The present prospective observational study comprised 113 patients (184 eyes) with newly diagnosed CMVR, from May 2008-March 2010. Each patient was followed-up every 3 months with medical history and ophthalmologic examination. Patients were divided as visual impairment and legal blindness. RESULTS : The majority of the patients were native Thai (91%), while the rest was of hill tribe origin. 55% were females with age ranged between 14-57 years (average of 39). The main cause of HIV infection was heterosexual contact (90%), followed by homosexual contact (7%). It was found that 68% had CD4 T-cell count less than 50 cells/microl and that 46% had bilateral CMVR. Major causes of visual impairment were CMVR zone 2&3, CMVR zone 1 and cataract, respectively. Major causes of legal blindness were CMVR zone 2&3, CMVR zone 1 and retinal detachment, respectively Retinal detachment was a major risk factor in both groups. Even when surgery was successful, the visual acuity was not significantly improved, indicating a permanent loss of vision. CONCLUSIONS : In the HAART era, immune recovery of HIV patients also helps restoring specific anti-CMVimmunity. HAART reduces occurrence of visual impairment to 0.10/eye-year (EY) and legal blindness to 0.15/EY, compared to the pre-HAART figures of 0.94-0.98/EY and 0.47-0.49/EY respectively. However, it did not completely eliminate the occurrence. CMVR and cataract remain the most common causes of visual acuity loss followed by retinitis-related retinal detachment, and optic nerve atrophy respectively.